Morpho-Anatomical and Physicochemical Standardization of Diospyros malabarica (Desr.) Kostel Stem Bark - Prakash, Chandra Gupta; Ashish, Kar; Nisha, Sharma; Nikunj, Sethi; Dipankar, Saharia; Naba, Kr. Goswami (Journal of Advances in Plant Biology, 2018)
Diospyros malabarica (Desr.) Kostel synonym Diospyros peregrina Gurke (Family: Ebenaceae) is a medium sized evergreen tree commonly known as Kendu in Assamese. The plant has ethnomedicinal significance and used by various ethnic communities of North-East India to treat various disorders like dysentery, diabetes, diarrhea malaria, ulcer and wounds. However, detailed scientific information is not available to identify the plant material, in order to ascertain its quality and purity. Therefore, the present work was carried out to perform morpho-anatomical and physicochemical analysis of D. malabarica stem bark. The bark is externally dark brown to black in color and rough having characteristics odor and astringent taste. The microscopy of bark reveals the presence of polygonal thick walled cork, 3-4 layered phellogen, 7-8 layered phelloderm, stone cells, phloem fibers and medullary rays. Stem bark powder showed thick walled cork cells, thick walled elongated phloem fibers, lignified stone cells and rhomboidal crystals of calcium oxalate. Further, physicochemical analysis of the bark power showed loss on drying, total ash, water soluble ash, and acid insoluble ash as 6.2, 5.6, 1.1, 2.45, and 5.7% w/w respectively. The alcohol and water soluble extractives values of the stem bark were 10.6 and 16.8% w/w respectively. The result of preliminary phytochemical screening indicates presence of triterpenoids, saponins, tannins, flavonoids and sterols. The findings of this study will facilitate pharmacognostic standardization of the plant material and aid in the preparation of an herbal monograph for the species.
Keywords: Diospyros malabarica; Pharmacognosy; microscopy; standardization; physicochemical